SOSIALISASI DAN PELATIHAN PEMBUATAN COOKIES DAN PERMEN JELLY (GUMMY) YANG TERBUAT DARI EKSTRAK TEMULAWAK DAN MADU - Novikasari, Linawati; Setiawati, Setiawati; Nofita, Nofita; Saputra, Muhammad Rio; Agustiansyah, Ferdika (Jurnal Abdimas Bina Bangsa, 2024)
One effort that can be made to improve people's health through traditional methods is by consuming honey and ginger. Temulawak is a traditional medicine that can increase and improve appetite. Honey has high levels of glucose and fructose which facilitate absorption in the small intestine and stimulate digestion to work better. Giving honey and ginger together regularly can potentially increase appetite or appetite so that food is fulfilled and weight gain occurs. The implementation method used in this activity is the RRA (Rapid Rural Appraisal) method. Respondents' knowledge regarding the benefits and methods of processing cookies and jelly candy (gummy) increased by 85%, 80% of respondents liked cookies and 85% of respondents liked gummy made from ginger extract and honey. It is hoped that this activity can be implemented by administrators and orphanage children so that it can increase children's appetite